CAPRA-S predicts outcome for adjuvant and salvage external beam radiotherapy after radical prostatectomy - Zimmermann, Michel; Delouya, Guila; Alenizi, Abdullah M.; Rajih, Emad; Zorn, Kevin C.; Taussky, Daniel (Canadian Urological Association Journal, 2016)
Introduction: We aimed to evaluate the predictive value of the Cancer of the Prostate Risk Assessment Postsurgical Score (CAPRA-S) for patients treated with radical prostatectomy followed by subsequent external beam radiotherapy (EBRT). Methods: A total of 373 patients treated with EBRT between January 2000 and June 2015 were identified in the institutional database. Followup and complete CAPRA-S score were available for 334 (89.5%) patients. CAPRA-S scores were sorted into previously defined categories of low- (score 0‒2), intermediate- (3‒5), and high-risk (6‒12). Time to biochemical recurrence (BCR) was defined as prostate-specific antigen (PSA) >0.20 ng/mL after EBRT. Survival analyses were performed using the Kaplan-Meier method and comparisons were made using the log-rank test. Results: Overall median time from surgery to EBRT was 18 months (interquartile range [IQR] 8‒36) and median followup since EBRT was 48 months (IQR 28‒78). CAPRA-S predicted time to BCR (<0.001), time to palliative androgen-deprivation therapy (ADT) (p=0.017), and a trend for significantly predicting overall survival (OS, p=0.058). On multivariate analysis, the CAPRA-S was predictive of time to BCR only (low-risk vs. intermediate-risk; hazard ratio [HR] 0.14, 95% confidence interval [CI] 0.043‒0.48, p=0.001). The last PSA measurement before EBRT as a continuous and grouped variable proved highly significant in predicting all outcomes tested, including OS (p≤0.002). Conclusions: CAPRA-S predicts time to BCR and freedom from palliative ADT, and is borderline significant for OS. Together with the PSA before EBRT, CAPRA-S is a useful, predictive tool. The main limitation of this study is its retrospective design.